Pengaruh Perencanaan Pajak, Leverage dan Good Corporate Governance terhadap Nilai Perusahaan - Lydia Shinta Uli; Prita Andini (Pusat Riset dan Inovasi Nasional, 2024)
This reseacrh aims to determine the influence of tax planning, leverage, audit committee, independent commissioners, managerial ownership, institutional ownership on firm value. The sample selection technique in this research used purposive sampling and obtained 22 food and beverage companies listed on the Indonesia Stock Exchange for the 2019 – 2022 period. The data analysis used in this research is multiple linear regression analysis using SPSS version 26 software. Based on the research results, it can be concluded that Institutional Ownership has a positive and significant effect on firm value. while Tax Planning, Leverage, Audit Committee, Independent Commissioners and Managerial Ownership have no effect on firm value.